2013
DOI: 10.1186/2045-8118-10-15
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cystatin C functional activity in the cerebrospinal fluid of amyotrophic lateral sclerosis and control subjects

Abstract: BackgroundCystatin C is a constitutively expressed and abundant cysteine protease inhibitor within the cerebrospinal fluid (CSF). Recent studies have reported a significant reduction in cystatin C concentration in the CSF of patients with amyotrophic lateral sclerosis (ALS) and several other neurodegenerative diseases, relative to healthy controls. Cystatin C can exhibit both neuroprotective and neurotoxic properties, suggesting that altered CSF cystatin C concentrations could potentially impact the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Haptoglobin is an acute phase protein 96-98 and cystatin C is a proteinase inhibitor abundant in CSF. 99-101 In this study, these proteins were only upregulated in corticosteroid-treated CSM-affected dogs, which is consistent with a corticosteroid-related increased as described in other studies. 102-104 Transthyretin is a neuroprotective negative acute phase protein and it is often downregulated in human neurological diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Haptoglobin is an acute phase protein 96-98 and cystatin C is a proteinase inhibitor abundant in CSF. 99-101 In this study, these proteins were only upregulated in corticosteroid-treated CSM-affected dogs, which is consistent with a corticosteroid-related increased as described in other studies. 102-104 Transthyretin is a neuroprotective negative acute phase protein and it is often downregulated in human neurological diseases.…”
Section: Discussionsupporting
confidence: 92%
“…We previously reported that NEP cleaved the Tyr 4 -Ile 5 bond of ANG-(1-7) in the BBM fraction from rat kidney (3); however, NEP is a metallopeptidase that is insensitive to thiol inhibitors such as PCMB, and the specific NEP inhibitor SCH39370 did not attenuate the metabolism of ANG-(1-7) (data not shown). Other thiol-sensitive peptidases localized in CSF include cystatin C, cathepsins, and papain, but their participation in the hydrolysis of ANG-(1-7) to ANG-(1-4) has not been described in CSF (45,63,80). Moreover, we have not established whether the thiol-sensitive peptidase is released from choroid or brain tissues.…”
Section: Control Bmxmentioning
confidence: 67%
“…Use of CSF, a nervous system indicator of growing interest in ALS (Sussmuth et al, 2008; Gladman et al, 2012; Mendonca et al, 2012; Tarasiuk et al, 2012; von Neuhoff et al, 2012; Wilson et al, 2013; Winer et al, 2013), as a biomarker of exposure rather than peripheral indicators such as blood or toenails is an additional strength of the present study. In our recent study on the relation among CSF and other indicators in neurologically healthy subjects (Solovyev et al, 2013), positive associations between CSF and blood levels were found only for Se-GPx, Se-TrxR and Se-HAS, while there was little or no correlation between CSF and blood levels for other organic forms such as SePP, for selenite and selenate (correlation coefficients −0.03 and 0.23, respectively, unpublished data by N. S. and B. M.), and total Se.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a case-control study to examine the hypothesis that Se species and particularly the inorganic ones are associated with ALS risk by using a CNS biomarker of exposure, cerebrospinal fluid (CSF), which appears to play a key role in assessing exposure to etiopathogenetic and therapeutic factors in this disease (Tarasiuk et al, 2012; von Neuhoff et al, 2012; Wilson et al, 2013; Winer et al, 2013). …”
Section: Introductionmentioning
confidence: 99%